Wiskott–Aldrich syndrome in a child presenting with macrothrombocytopenia. (19th May 2017) - Bastida, Jose Maria; Del Rey, Monica; Revilla, Nuria; Benito, Rocio; Perez-Andrés, Martin; González, Berta; Riesco, Susana; Janusz, Kamila; Padilla, Jose; Hortal Benito-Sendin, Ana; Bueno, David; Blanco, Elena; et al.
Abstract: Wiskott–Aldrich syndrome (WAS) is a rare X-linked recessive disease resulting from variants in the WAS gene, characterized by a triad of immunodeficiency, eczema, and thrombocytopenia. Despite the fact that WAS is traditionally differentiated from immune thrombocytopenia (ITP) by small size of WAS platelets, in practice, microthrombocytopenia may occasionally not be present, and in certain cases, WAS patients exhibit some parallelism to ITP patients. We characterized one patient presenting with the classic form of the disease but increased mean platelet volume. Molecular studies revealed a novel hemizygous 1-bp deletion in WAS gene, c.802delC, leading to a frameshift and stop codon at amino acid 308 (p.Arg268Glyfs*40). Next-generation sequencing of a total of 70 additional genes known to harbor variants implicated in inherited platelet disorders did not identify additional defects. The pathogenesis of macrothrombocytopenia in this case is not known, but probably the coexistence of a still unidentified additional genetic variant might be involved.